A zero-sum game or an interactive frame? Iron competition between bacteria and humans in infection war. Issue 16 (20th August 2022) - Wu, Zhenchao; Shao, Jiqi; Zheng, Jiajia; Liu, Beibei; Li, Zhiyuan; Shen, Ning
Abstract : Abstract: Iron is an essential trace element for both humans and bacteria. It plays a vital role in life, such as in redox reactions and electron transport. Strict regulatory mechanisms are necessary to maintain iron homeostasis because both excess and insufficient iron are harmful to life. Competition for iron is a war between humans and bacteria. To grow, reproduce, colonize, and successfully cause infection, pathogens have evolved various mechanisms for iron uptake from humans, principally Fe 3+ -siderophore and Fe 2+ -heme transport systems. Humans have many innate immune mechanisms that regulate the distribution of iron and inhibit bacterial iron uptake to help resist bacterial invasion and colonization. Meanwhile, researchers have invented detection test strips and coupled antibiotics with siderophores to create tools that take advantage of this battle for iron, to help eliminate pathogens. In this review, we summarize bacterial and human iron metabolism, competition for iron between humans and bacteria, siderophore sensors, antibiotics coupled with siderophores, and related phenomena. We also discuss how competition for iron can be used for diagnosis and treatment of infection in the future.